Intercultural sensitivity as a pathway to support students' cultural competence and identity formation in virtual exchanges - Rogler, Andreas; Wang, Lijuan; Uematsu-Ervasti, Kiyoko (Journal of International Students, 2026)
Virtual exchanges are increasingly used to expand access to international education. This study explored how Japanese students experienced intercultural learning and identity development within a virtual exchange programme conducted at a Finnish university. Using the Intercultural Sensitivity Scale as an analytical lens, qualitative data were drawn from semistructured interviews with programme participants to investigate how virtual, multicultural environments shape students’ intercultural sensitivity and identity formation. The findings revealed that challenges related to interaction engagement, attentiveness and confidence were exacerbated by language barriers, differing communication norms, and the limitations of online learning environments. These factors significantly influence students’ capacity for meaningful intercultural engagement and identity exploration.